Vanderbilt Wellness Program: Model and Implementation Guide - Matthew Zackoff; Elizabeth Sastre; Scott Rodgers (Association of American Medical Colleges, 2012)
Abstract Introduction Since the development and implementation of the Vanderbilt School of Medicine Wellness Program, institutions across the country have been interested in developing similar programs. Some have developed their own systems to address medical student wellness while others have opted to incorporate the time-tested Vanderbilt model into the structure of their institution. We feel it is imperative to share the details of the creation and implementation of this wellness program such that other medical schools may benefit from this knowledge as they attempt to create wellness programs at their own institutions. We hope that institutions are able to make use of this guide as they initiate or expand medical student-wellness programming at their institutions. Methods Through an instructor's guide and an implementation handbook, this resource not only illustrates the Vanderbilt model for wellness programming, but offers a step-by-step approach for evaluating the needs of an institution and walks through the process of implementing the key components of a wellness initiative tailored to the institution's needs. Results It is our belief that the Vanderbilt School of Medicine Wellness Program has had a tremendous impact over its 5 years in existence and is a significant factor for many students' decisions to come to Vanderbilt. Students openly admit that the culture of wellness is what makes achieving a degree in medicine at Vanderbilt a unique experience. Studies of our program have demonstrated improvements in faculty/student relationships, increased physical activity among our students, and perceived decreases in student burnout. This translates to more effective residents and overall more successful physicians. Discussion Our handbook will serve as a key reference to which medical educators and administrators can look to in order to gain timely and valuable insight as they seek to create their own institution-sponsored wellness programs. While no wellness program thus far created is likely perfect, the distribution of this resource will enable interested leaders in student wellness to gain the guidance necessary to begin the task of improving student-wellness outcomes in undergraduate medical education. We also hope that the dissemination of this information promotes collective sharing of both pitfalls and successes in regards to the promotion of student wellness and thus continually improves our efforts to cultivate healthy future physicians.